Aço AISI 430 recoberto com cobalto de pilhas de celular: uso como interconector para pilhas a combustível de óxido sólido - Eric Masalha Garcia (2012)
In a world stage increasingly turned to cleaner sources of energy, Solid Oxide Fuel Cells (SOFC) are a great option. Besides having a high conversion efficiency of chemical energy into electrical energy (close to 80% considering the co-generation) the SOFC are very environmentally friendly because, considering hydrogen as fuel, the waste of the process is water vapor. Despite many advantages exhibited by the SOFC abig limiting factor in its manufacturing is still the cost of its components. Due to the high operating temperature of SOFC (between 600 and 1000 oC), its components must be carefully selected so as to withstand mainly the corrosion caused by the highly oxidizing atmosphere on the cathode side. The components that have higher criteria to be observed are the electrical interconnects. It is estimated that these materials satisfymore than 60% of the total cost of SOFC. In order to reduce the production cost of the electrical interconnects for SOFCs, in this study we used the AISI 430 stainless steel coated with a cobalt layer. The AISI 430 stainless steel was chosen because of its low cost compared to commercial alloys used as Crofer and Inconel. The coverage of cobalt was obtained from electrodeposition technique due to its versatility, low cost and easyadaptation to industrial scale. In addition to significantly improve corrosion resistance and conductivity, the electrodeposition of cobalt enabled the recycling of batteries depleted Li-ion cell phones. This was possible because the cobalt solution used for the electrodeposition was obtained by dissolving the cathode of the battery which is amixed oxide of cobalt and lithium (LiCoO2). Recycling of exhausted batteries of mobile phones is a topic of great environmental and economic. Thus, this paper presents a highly viable alternative to significantly reduce the production costs of SOFC while giving a simple solution to an extremely complex problem that is battery disposal.